2006
DOI: 10.1259/bjr/43441736
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-modulated radiation therapy in the treatment of gastric cancer: early clinical outcome and dosimetric comparison with conventional techniques

Abstract: The purpose of this study was to assess the efficacy and toxicity of intensity-modulated radiation therapy (IMRT) in the treatment of gastric cancer. Seven patients with gastric cancer were treated with IMRT. Six patients (all Stage III) received post-operative chemoradiotherapy with concurrent 5-fluorouracil and leucovorin. One received planned pre-operative radiation, though did not proceed to surgery. All patients were planned to receive 50.4 Gy in 1.8 Gy fractions. IMRT planning was compared with opposed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(102 citation statements)
references
References 18 publications
6
91
0
Order By: Relevance
“…All patients were treated in the clinical ward of the radiation oncology department, with strict clinical control and observation, and there were no interruptions to therapy, except in three cases with an IMRT delay of 2-3 days. Thus, therapy was more continuous than is usually achieved with con RT [7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients were treated in the clinical ward of the radiation oncology department, with strict clinical control and observation, and there were no interruptions to therapy, except in three cases with an IMRT delay of 2-3 days. Thus, therapy was more continuous than is usually achieved with con RT [7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…The standard target dose of 45 Gy far exceeds the tolerance of several surrounding, critical normal tissues (most notably the kidneys and liver). As a result, con RT volumes are often significantly influenced by the need to avoid potential kidney and liver damage, but the resulting underdosing of some parts of the target can compromise local control and survival [8].…”
Section: Introductionmentioning
confidence: 99%
“…IMRT and image-guided radiotherapy (IGRT) have been demonstrated to be feasible approaches for delivering chemoradiation with improved dose coverage to the target volumes, and further sparing of organs at risk [28][29][30][31]. In our center, IGRT with respiratory control (either by gating or breath-hold) has been implemented routinely since 2008, aiming to reduce the effect of organ motion.…”
Section: Secondary Malignancymentioning
confidence: 99%
“…In a study conducted by Minn et al (2010) liver doses were lower with IMRT while no statistically significant difference was observed for liver and PTV doses. Milano et al (2006) compared 2D, 3D and IMRT; PTV dose appeared better with IMRT and kidney and liver doses were lower. In a study by Alani et al (2009) comparing 3D and IMRT no significant difference was observed for PTV doses, IMRT was only marginally better than 3D conformal radiotherapy at protecting spinal cord and kidneys from radiation.…”
Section: Discussionmentioning
confidence: 99%